On the boundaries and zoning of the Caspian oil and gas province - Yu. A. Volozh; V. A. Bykadorov; M. P. Antipov; T. N. Kheraskova; I. S. Patina; I. S. Postnikova (Georesursy, 2024)
Despite the long history of geological exploration and scientific research in the Caspian region many issues of its oil and gas geological zoning remain controversial, including justification the boundaries of oil and gas provinces at the ancient and young platforms: PreCaspian, Ciscaucasia-Mangyshlak and North-Ustyurt. This paper discusses problems of the ancient and young platforms sedimentary cover’s oil and gas zoning using the example of Pre-Caspian region. It is proposed to carry out oil and gas geological zoning of these regions with taking into account the types of the Earth’s crust sections and sedimentary cover’s hydrocarbon systems types, as well as the types of the main oil and gas complexes’ structures. The type of the Earth’s crust section is crucial upon identification oil and gas provinces boundaries; the type of hydrocarbon systems is in the foreground when identifying sub provinces; and the boundaries of oil and gas regions are determined by the main types of oil and gas complexes’ sections and structures.In the Pre-Caspian province three sub-provinces are identified and their oil and gas potential is characterized. The proposed boundaries of the province closely coincide with the distribution contours of the Kungur saliferous strata with considerable thickness (hundreds of meters). Due to the lack of a clear structural boundary between the Paleozoic hydrocarbon systems the Pre-Caspian and Volga-Ural oil and gas provinces are proposed to be considered as a single marginal-continental oil and gas mega-province. The obtained materials and conclusions can serve as a basis for basin modeling and hydrocarbon resources forecast’s refinement.